Alternatif Strategi Penguatan Pendidikan Karakater melalui Pendekatan Broken Windows - Sutomo Sutomo (Institut Agama Islam Negeri Purwokerto, 2018)
This paper discusses the strategy of strengthening the character education of learners through broken windows approach. Character education is interpreted as a value education, character education, and moral education, whose purpose is to develop the ability of learners to make a decision of the good and bad, to maintain goodness and to realize the good in their daily life deeply. The main problem faced in the world of education today is the decline of moral values ​​and character of learners, ranging from the level of primary education to secondary education. The problem is a very distant portrait of the educational character that we expect together, from the case of the students torturing the teacher to death, the learner challenges the teacher, the parents of the learners persecute the teacher, friend bullying, harassment, violence, brawl, etc. These events will certainly not happen if all the citizens of the school care and can prevent it from the beginning. Broken Windows Theory is one of the alternative solutions to the problems that are engulfing education in Indonesia. The strategy of using this theory is by making early prevention of negative behavior that is considered small but the beginning of a larger behavior. Application of Broken Windows theory in the world of education is expected to form learners with better character.